B-Cell Activating Factor Profile and Quality of Life in Systemic Lupus Erythematosus Patients - Andri Reza Rahmadi; Habib Burahman; Nadia Gita Ghassani; Rachmat Gunadi Wachjudi; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2022)
Background: B-Cell Activating Factor (BAFF) is a cytokine that plays a role in systemic lupus erythematosus (SLE) pathogenesis. BAFF increases B cell function, which will affect disease activity. In addition to decreasing disease activity, good quality of life (QoL) is one of the goals to be achieved in SLE therapy, which is also affected by disease activity. The purpose of this study is to know the correlation of the BAFF profile with the QoL of SLE patients. Methods: This was a cross-sectional study using secondary data from a previous study. The subjects of this study were SLE patients who had visited the rheumatology outpatient clinic or were hospitalized in Hasan Sadikin Hospital Bandung from September 2016 until February 2017. Subjects were asked to complete the Short Form-36 and measure their BAFF level in serum. Demographic data were collected, and disease activity data were assessed by Mexican Systemic Lupus Erythematosus Disease Activity Index (MEX-SLEDAI). The statistical analysis used in this study was the Spearman test. Results: There was a positive correlation between BAFF and MEX-SLEDAI (r 0.238, p-value 0.038). There was also a negative correlation between MEX-SLEDAI and PCS, as well as the MCS score (r -0.392 and -0.371, p-value <0.05). Conclusion: BAFF levels will increase in higher disease activity which will affect a poorer quality of life.